The personality structure and mindfulness levels of football players: Enneagram theory - Mehmet Kara; Nuriye Şeyma Kara; Murat Genç (ROL Spor Bilimleri Dergisi, 2025)
Studying mindfulness levels and personality types in soccer players is crucial for understanding the psychological factors that influence athletic performance. This study investigated the relationship between soccer players’ mindfulness levels and enneagram personality types. Study involved 207 active licensed football players from Turkish clubs, comprising 38 females (mean age 18.78±3.23) and 169 males (mean age 22.68±6.31). The data collection process utilized the Enneagram Personality Test and Mindfulness Inventory for Sport. Correlation analysis revealed strong positive relationships between the perfectionist personality type and the compromising (r=0.63) and helping (r=0.60) personality types. The non-judgmental (r=-0.46) and refocusing (r=-0.43) sub-dimensions showed the strongest negative relationships. Multiple regression analyses were conducted using mindfulness sub-dimensions as dependent variables. The first model found significant predictors for achiever (β=0.233), authentic (β=0.169), and compromiser (β=0.219) personality types. The second model identified perfectionist (β=-0.238), authentic (β=-0.167), head (β=-0.191), and compromiser (β=-0.186) types. The third model found that achievers (β=0.241) and authentic (β=0.327) types were significant predictors. Enneagram personality types explained considerable variance in the mindfulness (R2=0.35), non-judgement (R2=0.23), and refocusing (R2=0.35) sub-dimensions. Regression analyses indicated that Enneagram personality types were significant predictors of athletes’ mindfulness (R² = 0.35), non-judgement (R² = 0.23), and refocusing (R² = 0.35) levels, with the achiever, authentic, and compromiser types being the most impactful predictors. These findings demonstrate that Enneagram Theory effectively elucidates the relationship between soccer players’ mindfulness levels and personality types, providing valuable insights for sports science literature.